The Improvement of Prospective Teachers' Life-long Learning during the Plant Diversity Course with 5E+e Inquiry - Muhammad Syaipul Hayat; Nuryani Rustaman; Adi Rahmat; Sri Redjeki (Scientiae Educatia: Jurnal Pendidikan Sains, 2020)
Not a few students who have difficulty interpreting the material being studied in terms of life encourage the need for a paradigm shift in science learning, which is directed at lifelong learning. In this paper, an entrepreneurship-oriented 5E (Engagement, Explain, Exploration, Elaboration, and Evaluation) inquiry learning program is developed, which is also often called 5E+e. This research investigates the improvement of lifelong learning for the prospective teachers during the 5E+e inquiry in the plant diversity course. The quasi-experimental method with a one-group pretest-postest design was used. The research subjects were taken by purposive sampling, namely the fifth-semester students of the Biology Education Study Program at one of the Teachers Institution in Central Java with 31 participants. Data were gathered using a questionnaire filled out by students before (pre) and after (post) the treatment of the 5E+e inquiry learning and observation. The data analysis was carried out in both quantitative and qualitative-descriptive manners to make a comprehensive conclusion. The results revealed that the average lifelong learning score of prospective teachers compiled with rubrics had increased between before (2.68) and after being given the program (3.26) with a maximum score of 4.00. Thus, it can be concluded that the entrepreneurship-oriented inquiry learning program applied to the plant diversity course can increase the lifelong learning of prospective teachers.